The application of integrative thinking to develop a stewardship-based broader collective bargaining framework for the South African automotive industry - Evertse, Johann Francois Lewis (Rhodes University, 2026)
The automotive industry is one of the largest industries in South Africa, making an important contribution to the country’s economy. The industry is also the most visible sector of the South African economy, attracting significant foreign direct investment, a key driver of economic growth and job opportunities. Despite the positive progress, the industry faces recent challenges, including slow economic growth, unstable electricity supply, international competitive-ness, the importation of cheaper vehicles from China and other Asian countries, and recent US trade tariff announcements. The country’s heavy reliance on the export of cars and components makes it vulnerable to global protectionist trends, such as trade tariffs and the AGOA pro-gramme. The aim of the research was to explore the development of a stewardship-based, broader collective bargaining framework to address the viability and socio-economic challenges facing the South African automotive industry through the application of interactive dialogue and integrative thinking. With respect to the methodological approach, the exploratory case study method was applied, as it best suited the exploration of stakeholders' interrelated activities and views. This method is multi-perspectival, in that the researcher considered not only the voices and perspectives of the parties involved in the challenge but also their interactions. The primary method of data collection involved conducting interviews with key stakeholder representatives from sector employer representative organisations, unions, industry business councils, and government, and applying thematic analysis to the data to generate codes and themes, ultimately yielding paradoxical statements. Two procedures were applied sequentially, namely interactive dialogue and integrative think-ing. Through interactive dialogue, participants representing parties involved in collective bar-gaining in the automotive industry debated the paradoxical statements arising from the challenges facing sector-wide collective bargaining and explored potential solutions to reduce these tensions. In the second step, through a process of integrative thinking, the researcher constructively reconciled the tensions between opposing solutions by generating a holistic model that incorporated elements of the respective solutions but went beyond their individual resolutions. This research illustrated the potential application of a collaborative stewardship approach be-yond traditional social-ecological sustainability issues to address the multiplicity of challenges in collective bargaining in the South African automotive industry. Considering the study's contributions to the body of knowledge, the following contributions were identified: (1) scholarly, depicting the application of a collaborative stewardship approach to a new context and the application of a highly centralised collective bargaining arrangement in the South African automotive industry; (2) methodological, covering the application of paradox theory and integrative thinking to interorganisational challenges with multiple stakeholders, and (3) practical, as to how collaborative stewardship approach was applied in addressing the multiplicity of challenges in collective bargaining in the South African automotive industry. The South African automotive industry has long been the cornerstone of South Africa’s manufacturing economy. Considering the future, sustaining and growing this sector requires a concerted effort from all stakeholders – industry, government, labour and society. However, the automotive sector faces numerous challenges, but also has opportunities beyond the current global manufacturing strategy afforded by exploring the African automotive market. The re-search suggests a stewardship approach in which leadership from all sectors of the industry collaborate across industries and borders to create a sustainable and growing automotive eco-system, not only in South Africa but throughout Africa.
Keywords: Collective bargaining (http://id.loc.gov/authorities/subjects/sh85027996); Automobile industry and trade (http://id.loc.gov/authorities/subjects/sh85010151); Management; Stewardship (https://www.wikidata.org/wiki/Q1543547); Corporatism (https://www.wikidata.org/wiki/Q192886); International competitiveness (https://www.wikidata.org/wiki/Q11742556); Viability study (https://www.wikidata.org/wiki/Q7924412)